Pattern of adverse drug reaction in geriatric inpatients of medicine in a tertiary care center: a prospective observational study - Parmar, Nikita A.; Panchal, Vishal; Jadav, Shilpa P. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Adverse drug reactions (ADRs) represent a major public health problem in older age. In order to better evaluate this problem, this study was designed to assess the prevalence and spectrum of ADRs in terms of frequency, type, severity and preventability in geriatric patients in medicine ward of Guru-Gobind Sing hospital, Jamnagar during 12 months study period. Methods: All ADR related patient’s necessary data was obtained and recorded on a pre- designed case record form (CRF). The data record includes general details e.g., name, age, sex, past and present history, general and systemic examination, laboratory investigation, diagnosis and treatment. Details regarding suspected medications, treatment given, and the outcome were documented with prior permission of institutional ethics committee. Results: Demographic analysis of prospective study revealed that out of 84 patients, 45 male and 39 were female. The patients had developed ADR within the age ranges of 31 (65-69) followed by 23 (75-79). The majority of ADR was vomiting and diarrhea 15 followed by chills 08 and cough 04. It is evident that antimicrobials 31 agents were mainly suspected followed by NSAIDs 18. According to WHO-UMC scale, the possible cases had a higher incidence 63, followed by probable 19 and certain 2. After estimating the severity by Hartwigs scale 79.8% were mild to moderate while 20.23% were severe in nature. Conclusions: Age is not an independent risk factor of ADRs and suitable monitoring and regular medication review can reduce the incidence of ADRs in geriatric people.